2006
DOI: 10.1002/nau.20257
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐A‐receptor antagonist LU 302146 inhibits electrostimulation‐induced bladder contractions in vivo

Abstract: In the presented animal model, ET-1 inhibition with the selective ET receptor-A-antagonist LU 302146 decreases stimulation-induced bladder contraction in vivo. The results suggest that the selective ET-A antagonist LU acts on the atropine-resistant component of efferent detrusor activation since additional administration of atropine almost completely abolish detrusor contraction. This observation in addition to the involvement of ET-1 in bladder smooth muscle proliferation, raises the possibility that ET-recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…As mentioned above, ET-1 can bind to specific receptors to exert multiple effects on bladder functions such as inducing detrusor overactivity and modulating sensory function in the peripheral nervous system. 25 , 27 , 48 , 49 This study also revealed the key role of endothelin pathway in the induction of bladder hypersensitization and hyperalgesia. In comparison with saline infusion, ET-1 infusion further significantly decreased the pressure to trigger PT and VMR, together with a more forceful and longer VMR.…”
Section: Discussionsupporting
confidence: 52%
“…As mentioned above, ET-1 can bind to specific receptors to exert multiple effects on bladder functions such as inducing detrusor overactivity and modulating sensory function in the peripheral nervous system. 25 , 27 , 48 , 49 This study also revealed the key role of endothelin pathway in the induction of bladder hypersensitization and hyperalgesia. In comparison with saline infusion, ET-1 infusion further significantly decreased the pressure to trigger PT and VMR, together with a more forceful and longer VMR.…”
Section: Discussionsupporting
confidence: 52%
“…This stimulation-induced rise in bladder pressure can be urodynamically evaluated and objectively quantified. Standardized stimulation parameters result in reproducible, stimulation-induced bladder contractions suitable for pharmacological evaluation of drug effects on bladder contraction [12] . In this study, the sacral root S2 was stimulated to evoke neurogenic-induced bladder contractions.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 is able to decrease the micturition volume, an effect that could be blocked by ET-receptor antagonists [47]. The selective ET-A-antagonist, LU 302146, reduced the stimulation-induced pig bladder contraction in an atropine-inhibited way [48]. Experiments with i.v.…”
Section: Neuropeptidergic Systemmentioning
confidence: 99%